Liberal Internationalism Theory, History, Practice - Jahn, B. (Palgrave Studies in International Relations, 2013)
This study provides an original conception of liberalism that accounts for its internal contradictions and explains the current crisis of liberal internationalism. Examining the disjuncture between liberal theory and practice, it offers a firmer grasp on the historical role of liberalism in world politics.